Respostas da comunidade de algas perifíticas sob diferentes intensidades de luz na lagoa da UFES (Vitória, ES) - Costa, Adriano Goldner (2011)
This study aimed to evaluate the responses ofperiphytic algae community under different light intensities during thesuccession in a shallow tropical lagoon(UFESlagoon, Vitória).An experimental structure containing glass slides as substratewasimplanted in the limnetic zone of the lagoon, where three treatments wereestablished: 100% of incident radiation; 30% shadingand 50% shading.Seven samplings were conducted withintervals of two to seven days, during 29 days of colonization.It wasdetermined: temperature (air / water), total suspended solids,turbidity, pH, alkalinity, depth, transparency, euphotic zone,dissolved oxygen, conductivity, salinity, chlorophyll aof water, ammoniacal nitrogen,nitrite, nitrate, orthophosphate, total phosphorusand orthosilicate.The climatological data (precipitation, air temperature, solar radiation and wind velocity) had been obtainedfrom the Incaper meteorological station.In situit was also determined the percentage ofincident radiation on subsurfaceofwater for each treatment.It evaluated the following attributes of the community: taxarichness,density, abundance, dominance, diversity,evenness, dry mass, ashfree dry mass,ashes, concentration of chlorophyll a, b, carotenoids, phaeopigments and chlorophylla:phaeopigmentsreason.Based on periphytic biomass,it wasapplied theLakatos index and the autotrophic index.It wasrecorded54 taxa of algae withqualitative predominanceof chlorophytes,cyanobacteria and diatoms.The pattern of succession of the community regardingrichness, density and biomass was similar between treatments,being determined principally by autogenic processes.However,higherrainfalland nutrient concentrationsfavored theincreaseof biomassand densityinthe final stages, when thedifferencesbetweentreatmentswere evident.The richnessandtotal densitywerelowerunderlowlight intensities.On the otherhandthe diversityandevennessdid notshowsensitive responses.The green algae showed greater contribution in the early stages of succession, being replaced by diatoms in the intermediate stages and by cyanobacteria in the final stages.Despite thesimilarityin thepatternof successionbetween treatments,chlorophytes(mainly represented byTetraedron minimum)anddiatoms(mainly represented byNitzchiapalea)showeda markedreductionindensityunderlowerlight intensities.At the level ofClass, cyanobacteria showed no preference in the face ofdifferent light conditions.However, at species level, Merismopediainsignisand Heteroleibleiniasp.grew better under lowerlight intensities.The concentrations of photosynthetic pigmentsshowed sensitive responses, increasing with greater shadingimposed by the treatments (photoacclimation).Dry mass,ashes andbiological indicesdid not differsignificantlybetweentreatments.ExceptionmadetotheautotrophicindexandtheLakatosindexbasedonchlorophylla,whichweresensitiveinthe final stagesof succession.The ash free dry mass, as well as density, responded inversely to the photosynthetic pigments, indicating a reduction in biomass production under increased shading.The results showed that the periphyton of UFES lagoon presents sensitive responses to different light intensities, contributing to the knowledge of the function of this variable as a factorcontroller of the community in tropical lentic systems